Morphological versus molecular identification of Culex annulirostris Skuse and Culex palpalis Taylor: key members of the Culex sitiens (Diptera: Culicidae) subgroup in Australasia. Issue 4 (23rd July 2013) - Jansen, Cassie C; Hemmerter, Stéphane; van den Hurk, Andrew F; Whelan, Peter I; Beebe, Nigel W
Abstract: Members of the Culex sitiens subgroup of mosquitoes are important arbovirus vectors in the Australasian region. However, some species in this group, particularly Cx. annulirostris and Cx. palpalis, are difficult to distinguish based on morphological characters alone. We evaluated the reliability of morphological characters commonly used in taxonomic keys against a PCR‐based diagnostic tool that examined the ribosomal ITS1 gene region. Although reliable morphological characters allow identification, molecular identification remains the most accurate means for distinguishing Cx. annulirostris and Cx. palpalis .